A Systematic Review of Commercialization of Public Enterprises in Global North and South - Ngozi Okwuchukwu OKEKE; Daniel Eseme GBEREVBIE (Covenant University Journal of Politics and International Affairs, 2023)
Commercialisation is a deliberate government strategy that aims to increase economic development and efficiency by lowering government involvement and expanding the range of activities performed by the private sector through the transmission of government-owned assets to private ownership, and promoting the participation of private stratum in public activity. This study therefore aims to analyse the introduction of commercialisation in countries both in the global north and global south. This study also aims to unravel the merits and demerits of commercialisation as well as the factors that led to the success or failure of the commercialisation process in the countries listed. The study engaged secondary data while it adopted the liberal theory and a descriptive survey research design. For this study, secondary data were collected from published works, academic journals, books, reports, and online materials. Findings revealed that following the ostensibly successful commercialisation programme in Britain, the commercialisation of public businesses has emerged as a key policy tool in countries both in global south and global north. This study concludes generally, that the commercialisation policy itself is not a terrible notion, but that the issue is more with its implementation and the practical effects it has on the country’s economic independence.